2012
DOI: 10.1523/jneurosci.5358-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Vision for Action in the Macaque Medial Posterior Parietal Cortex

Abstract: Area V6A encodes hand configurations for grasping objects (Fattori et al., 2010). The aim of the present study was to investigate whether V6A cells also encode three-dimensional objects, and the relationship between object encoding and grip encoding. Single neurons were recorded in V6A of two monkeys trained to perform two tasks. In the first task, the monkeys were required to passively view an object without performing any action on it. In the second task, the monkeys viewed an object at the beginning of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 62 publications
10
73
0
1
Order By: Relevance
“…Recently, it has been suggested that also the posterior parietal area V6A, which was known to contain visual as well as reaching neurons , could be implicated in the control of grasp . Because many V6A neurons displayed visual selectivity during passive fixation of objects of different shapes (Fattori, Breveglieri, Raos, Bosco, & Galletti, 2012), it was suggested that this visual selectivity subserves the computation of object affordances, but at present there are only indirect evidences supporting this view (see Fattori et al, 2012). In the present work, we aimed to check whether the visual selectivity observed in V6A reflects a pure visual analysis of objects or is an expression of an encoding of object affordance.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recently, it has been suggested that also the posterior parietal area V6A, which was known to contain visual as well as reaching neurons , could be implicated in the control of grasp . Because many V6A neurons displayed visual selectivity during passive fixation of objects of different shapes (Fattori, Breveglieri, Raos, Bosco, & Galletti, 2012), it was suggested that this visual selectivity subserves the computation of object affordances, but at present there are only indirect evidences supporting this view (see Fattori et al, 2012). In the present work, we aimed to check whether the visual selectivity observed in V6A reflects a pure visual analysis of objects or is an expression of an encoding of object affordance.…”
Section: Introductionmentioning
confidence: 84%
“…Population response was calculated as averaged spike density function (SDF; Gaussian kernel, half-width 40 msec) as detailed in Fattori et al (2012). To statistically compare the different SDFs, we performed a permutation test using the sum of squared errors as the test statistic .…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the kinematics of reaching‐only action, as well as the amplitude and the latency of P300 and N400 ERP components in parietal and prefrontal sites, respectively, were modulated by object size, consistent with physiological findings on nonhuman primates (Fattori et al. 2012). The discrepancy between these and our findings could rely on the better temporal resolution provided by ERPs with respect to fMRI, and might suggest that object size, or more precisely the level of accuracy of the movement determined by it, could modulate reaching‐only actions on a temporal, rather than a spatial basis.…”
Section: Discussionmentioning
confidence: 99%
“…(2014) showed that the kinematics of reaching‐only, as well as the amplitude and the latency of P300 and N400 ERP components in parietal and prefrontal sites, respectively, were modulated by object size, consistent with physiological findings on nonhuman primates (Fattori et al. 2012). The possibility to shed further light on these issues is offered by a multivariate approach that exploits multivoxel pattern analysis (MVPA; e.g., Di Bono and Zorzi 2008; O'Toole et al.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, neurons in V6A area have been found to contextually encode different representations of the target position, allowing for easy reference frame transformations In V6A, neurons with retinotopically organized receptive fields are modulated by gaze direction in order to encode spatial positions [35], [36]. Moreover, V6A has proprioceptive properties, and is directly involved in the execution of reaching and grasping movements [37], in accordance with its role in reference frame transformations between eye-centered, body-centered, and hand-centered representations [12], [38], [39]. Once these frames of reference (f.o.r.)…”
Section: Neuroscience Backgroundmentioning
confidence: 99%